Value Creation in Triadic Business Relationships: Interaction, Interconnection and Position - Mette Vedel (Copenhagen Business School (CBS), 2010)
This thesis reports the findings of one of three co-financed research projects under the heading: “Customer driven innovation in the building articles industry”. The issue is value creation in triadic business relationships, and the aim is to explore in what ways the expansion from a dyadic level of analysis to the level of micro-networks can inform our understanding of value creation in intermediated systems.
hdl:10398/8165
Keywords: 650